¿De qué hablan? discursos editorialistas en Centroamérica - López, Edi Efrain Bámaca (2018)
The objective of the present work is to analyze the editorial discourse of written media in Guatemala (Prensa Libre), Salvador (La Prensa Gráfica), Honduras (La Tribuna) and Nicaragua (La Prensa) and determine the importance of discourse on climate change. In response, 168 editorials were analyzed from the technique of constructing weeks, which consists of choosing one week per month, with days not repeated. They are analyzed under a Bakhtinian look; which emphasizes the compositional form and thematic unity. It is denoted that the majority’s editorial emphasis is on subjects related to politics, economics, and violence, especially. Despite the cause of the increasing climatic change, is of anthropic origin, the speech is null. There is no assertive speech about it.